ANALISIS SPASIAL KEJADIAN PENYAKIT LEPTOSPIROSIS DI KABUPATEN SLEMAN PROPINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2011 - Febrian, Ferry; Solikhah, Solikhah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2013)
AbstractBackground: Leptospirosis is an acute infectious disease that can infect humans and animals (zoonoses). The cause of the disease is Leptospira. Leptospirosis is spread all over the world, including Indonesia. One area in Yogyakarta Province is a region of leptospirosis is endemic to the events Sleman District cases constantly increasing. Spatial analysis is an analysis and description of the geography of disease data with regard to population distribution, the distribution of environmental risk factors, ecosystem, social and economic, as well as analysis of relationships between variables. Objective to analyze the incidence of the disease leptospirosis spatially and risk factors Sleman District of Yogyakarta Province in 2011.Methods: The study was descriptive research aimed to describe and either map leptospirosis disease events in Sleman District of Yogyakarta Province in 2011. The data used in this research was from the Sleman District Health Office. Sample size of this research was 61 leptospirosis patients.Results: Patients with leptospirosis was highest in Moyodan. Spatial analysis showed most leptospirosis occurs in locations with pet ownership (59,1%), the presence of rat (85,2%), vegetation (100%), and occurred in the location of the trenches / ditches around the house (47,5%).Conclusion: It should be done to inform the public about the disease leptospirosis, and Public Health Service Sleman need to develop early warning systems (SKD) so that more optimal disease eradication.Keywords : zoonoses, leptospirosis, spatial analysis, risk factors.